Management of Utilization of Chemistry Laboratory Based on Instructional Group Classroom to Support the Learning Process (Educational Management, 2022)
The chemical laboratory is one type of laboratory that is considered important in the implementation of education, research, and community service so that special management is needed. Chemical laboratory management is the main goal so that activities in the chemistry laboratory can run smoothly. Managers and users of the laboratory must have good cooperation, always communicate between laboratory institutions, and be broad-minded so that any difficulties can be solved / resolved properly. Managers and users of chemical laboratories must understand chemical laboratory management techniques to support the learning process. The purpose of this study is to understand the utilization management of the Classroom Instructional Group-based chemistry laboratory and analyse the feasibility of the IGC-based chemical laboratory management engineering guidebook to support the learning process. The chemical laboratory is one type of laboratory that is considered important in the implementation of education, research, and community service so special management is needed. Based on the results of preliminary observations, there are schools that have not utilized the chemistry laboratory to the fullest. Laboratory management is needed so that practical learning in the chemistry laboratory can run effectively. The management of the utilization of this chemical laboratory includes planning, organizing, actuating, and controlling (POAC). This study uses a qualitative descriptive approach to explain the management of the use of IGC-based chemistry laboratories and the 4D (four D) model to analyse the feasibility of IGC-based chemistry laboratory management handbooks to support the learning process. Research data were obtained from the results of observations, interviews, and documentation. The subjects of this study were teachers, laboratory workers, and students. The feasibility level of the IGC-based laboratory management engineering guidebook is determined through 6 product assessment activities, namely from the assessment results of material experts, media experts, peer reviewers, chemistry teachers, laboratory personnel, and student responses. Based on the results of the assessment, it can be concluded that the IGC-based laboratory management engineering guidebook is feasible and suitable for use as a medium to support the student learning process. The feasibility level of the IGC-based laboratory management engineering guidebook is determined through 6 product assessment activities, namely from the assessment results of material experts, media experts, peer reviewers, chemistry teachers, laboratory personnel, and student responses. The results of the assessment conducted by material experts obtained a feasibility level of 82.9% in the decent category. The results of the research by media experts obtained a feasibility level of 82.5% in the decent category. The assessment results from peer reviewers obtained a feasibility level of 85.1% in the decent category. The assessment results from chemistry teachers obtained a feasibility level of 85.4% in the decent category. The assessment results of the laboratory personnel obtained a feasibility level of 85.8% in the decent category. At the stage of large-scale dissemination of the assessment products from chemistry teachers obtained a feasibility assessment of 92.5% in the decent category. The results of the assessment from laboratory personnel obtained a feasibility assessment of 91.25% in the decent category. The results of the student response assessment obtained a feasibility level of 95.6% in the decent category. Based on the results of the assessment, it can be concluded that the IGC-based laboratory management engineering guidebook is feasible and suitable for use as a medium to support the student learning process.